Targeted GC-MS analysis of firefighters' exhaled breath: Exploring biomarker response at the individual level. Issue 5 (4th May 2019) - Wallace, M. Ariel Geer; Pleil, Joachim D.; Oliver, Karen D.; Whitaker, Donald A.; Mentese, Sibel; Fent, Kenneth W.; Horn, Gavin P.
Abstract: Biomarker measurements can provide unambiguous evidence of environmental exposures as well as the resultant biological responses. Firefighters have a high rate of occupational cancer incidence, which has been proposed to be linked in part to their increased environmental exposure to byproducts of combustion and contaminants produced during fire responses. In this article, the uptake and elimination of targeted volatile organic compounds were investigated by collecting the exhaled breath of firefighters on sorbent tubes before and after controlled structure burns and analyzing samples using automated thermal desorption-gas chromatography (ATD-GC/MS). Volatile organic compounds exposure was assessed by grouping the data according to firefighting job positions as well as visualizing the data at the level of the individual firefighter to determine which individuals had expected exposure responses. When data were assessed at the group level, benzene concentrations were found to be elevated post-exposure in both fire attack, victim search, and outside ventilation firefighting positions. However, the results of the data analysis at the individual level indicate that certain firefighters may be more susceptible to post-exposure volatile organic compounds increases than others, and this should be considered when assessing the effectiveness of firefighting protective gear. Although this work focuses on firefighting activity, the results can be translated to potential human health and ecological effects from building and forest fires.